Controlling cell division in yeast and animals: does size matter? - Grewal, Savraj S (BioMed Central, 2003)
In yeast, cell-size checkpoints coordinate cellular growth with cell-cycle progression. Now, evidence has been provided that such checkpoints probably do not exist in mammalian cells. These findings highlight an important difference between how yeast and animal cells proliferate in response to extracellular cues.